Sepakbola dan Kefanatikan: Kontruksi Makna Liverpool FC Bagi Seorang Bigreds Bogor - Muhammad Iqbal Muharram; Yanti Tayo; Oky Oxcygentri (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study has an identification problem that seeks to find out the meaning of Liverpool FC for a Bigreds, as well as looking for a motive for a Bigreds who is in Bogor. The phenomenon of a fan supporting his team has been around researchers, especially Liverpool FC. But not many know how a Bigreds defines Liverpool FC club for themselves, and what their motives are to become a Bigreds. This study uses a qualitative method and a phenomenological approach, because in this study the researcher examines a phenomenon with the aim of finding out the meaning and motives of a Bigreds. This research is going well, researchers must examine in depth so that the informants provide true information. The theory used in this research is Alfred Schutz's phenomenological theory. The results of this study are Bigreds interpret Liverpool FC as their self-concept and their love for their proud club. The informant's motive for becoming a Bigreds is based on family motives and social motives. Keywords: phenomenology, motive, meaning